Whole Life Design and Resource Reuse of an Integrated Collector-Storage Solar Water Heater. Issue 1 (14th February 2019) - Saint, Ruth M; Pomponi, Francesco; Garnier, Celine; Currie, John I
Abstract : Passive solar systems are often designed primarily with efficiency in mind and research efforts are concentrated towards gaining an increase in performance. However, due to the multiple materials used, their manufacturing processes, a lifespan that is usually shorter than that of a building a system is applied to, and the waste generated when it has reached the end of its useful life, a more holistic approach to the design and performance of these systems should be adopted. This paper reports on the environmental impact of a unique integrated collector-storage solar water heater (ICSSWH) design, experimentally tested under Scottish weather conditions, considering circular economy and reuse potential. As such, the material flows and components used are mapped against the life-cycle stages of existing European standards, whilst ensuring an optimal efficiency. End-of-life considerations and design for disassembly and reuse are assessed and discussed. Energy payback times of 4.5 and 4.6 years can be realised for a circular and linear approach, respectively. Operational carbon savings, which far outstrip the embodied carbon, demonstrate carbon payback times of just 7 months, when replacing an electric system. The results show that a holistic design, which promotes circular economy principles, does not compromise efficiency and economic viability.